TEACHING WRITING DESCRIPTIVE TEXT THROUGH RESPONDED THEMATIC WRITING TASK - Laila Wati; Siti Husna Maab; Hamzani Wathoni; Siti Maysuroh; Ari Prasetyaningrum (English Education Department, 2022)
This study aims at finding the effectiveness of Responded Thematic Writing Tasks in teaching writing descriptive text to develop students’ fluency in writing. This research is a pre-experimental research with pretest-posttest design. The sample of this research was 32 students of semester 2A of Study Program of English Language Education of Hamzanwadi University in the academic year 2021-2022. A writing test was used to collect the data. The data were then analyzed by using descriptive statistic, and paired sample T-test was used to test the hypothesis. Based on the result of the study, the mean score of the pretest was 63.28 while the posttest was 78.75. This shows that the mean score in the posttest was higher than the mean score in the pretest. Additionally, the sig score was at 0.00 < 0.05, so the hypothesis (Ha) of this study was accepted. It implies that Responded Thematic Writing Tasks was significantly effective in developing students’ fluency in writing descriptive text. It is suggested that English teacher use Responded Thematic Writing Tasks as an alternative technique in teaching writing.